Haemophilus haemolyticus Interaction with Host Cells Is Different to Nontypeable Haemophilus influenzae and Prevents NTHi Association with Epithelial Cells - Pickering, Janessa L.; Prosser, Amy; Corscadden, Karli J.; de Gier, Camilla; Richmond, Peter C.; Zhang, Guicheng; Thornton, Ruth B.; Kirkham, Lea-Ann S. (Frontiers in Cellular and Infection Microbiology, 2016)
Nontypeable Haemophilus influenzae (NTHi) is an opportunistic pathogen that resides in the upper respiratory tract and contributes to a significant burden of respiratory related diseases in children and adults. Haemophilus haemolyticus is a respiratory tract commensal that can be misidentified as NTHi due to high levels of genetic relatedness. There are reports of invasive disease from H. haemolyticus, which further blurs the species boundary with NTHi. To investigate differences in pathogenicity between these species, we optimized an in vitro epithelial cell model to compare the interaction of 10 H. haemolyticus strains with 4 NTHi and 4 H. influenzae-like haemophili. There was inter- and intra-strain variability but overall, H. haemolyticus had reduced capacity to attach to and invade nasopharyngeal and bronchoalveolar epithelial cell lines (D562 and A549) within 3h when compared with NTHi. H. haemolyticus was cytotoxic to both cell lines at 24h, whereas NTHi was not. Nasopharyngeal epithelium challenged with some H. haemolyticus strains released high levels of inflammatory mediators IL-6 and IL-8, whereas NTHi did not elicit an inflammatory response despite higher levels of cell association and invasion. Furthermore, peripheral blood mononuclear cells stimulated with H. haemolyticus or NTHi released similar and high levels of IL-6, IL-8, IL-10, IL-1β and TNFα when compared with unstimulated cells but only NTHi elicited an IFNγ response. Due to the relatedness of H. haemolyticus and NTHi, we hypothesized that H. haemolyticus may compete with NTHi for colonization of the respiratory tract. We observed that in vitro pre-treatment of epithelial cells with H. haemolyticus significantly reduced NTHi attachment, suggesting interference or competition between the two species is possible and warrants further investigation. In conclusion, H. haemolyticus interacts differently with host cells compared to NTHi, with different immunostimulatory and cytotoxic properties. This study provides an in vitro model for further investigation into the pathogenesis of Haemophilus species and the foundation for exploring whether H. haemolyticus can be used to prevent NTHi disease.